2014
DOI: 10.1155/2014/214510
|View full text |Cite
|
Sign up to set email alerts
|

Size, Temperature, and Strain‐Rate Dependence on Tensile Mechanical Behaviors of Ni3Sn4 Intermetallic Compound Using Molecular Dynamics Simulation

Abstract: This study focuses on exploring the mechanical properties and nonlinear stress-strain behaviors of monoclinic Ni3Sn4single crystals under uniaxial tensile test and also their size, temperature, and strain-rate dependence through constant temperature molecular dynamics (MD) simulation using Berendsen thermostat. The deformation evolution of the Ni3Sn4atomic nanostructure during the tensile test is observed. In addition, the tensile yield strains of various Ni3Sn4single crystals at different strain rates and tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…It is always necessary to understand a material's behavior under certain conditions so that we get necessary information for using the material as a component in nano-mechanical application [36][37][38]. The materialistic information can be extracted from multiple set of repetitive experimentation/ computation or we can adopt a statistical method.…”
Section: Resultsmentioning
confidence: 99%
“…It is always necessary to understand a material's behavior under certain conditions so that we get necessary information for using the material as a component in nano-mechanical application [36][37][38]. The materialistic information can be extracted from multiple set of repetitive experimentation/ computation or we can adopt a statistical method.…”
Section: Resultsmentioning
confidence: 99%
“…Their explanation was mainly concentrated on the IMCs' inherent brittleness. Actually, the IMCs were well known to possess considerably higher tensile strength than Sn-based solder materials, i.e., 2.0-5.1 GPa for Ni 3 Sn 4 intermetallic and 86.1-96.7 MPa for Sn-rich solder [30,31]. Ho et al [32] and Glenn et al [33] reported that the presence of voids into the IMCs is a mainly influential factor in causing the joint rapid fracture due to low fracture toughness of IMCs.…”
Section: Influences Of Imc Microstructure Evolution On Tensile Mechanmentioning
confidence: 99%
“…To maintain a constant temperature in the system, bath relaxation time was introduced into the calculation. We applied the Berendsen thermostat [38][39][40][41] to the trajectory calculations under the chosen thermal conditions.…”
Section: Direct Aimd Calculations From Thermal Activation Regionmentioning
confidence: 99%